Analisis Efektivitas Peranan Strategis Dinas Koperasi dan UKM dalam Upaya Pelaksanaan Program Pengembangan UMKM di Kabupaten Sikka - Maria Advensia Tia; Wilhelmina Mitan; Paulus Libu Lamawitak (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aims to determine the effectiveness analysis of the strategic role of the Department of Cooperatives and SMEs in implementing the UMKM development program in Sikka Regency. Data analysis uses Qualitative Analysis with the interview method. The results of this research show that, firstly, the strategic role carried out by the District Cooperatives and SMEs Service. Sikka is education and training which aims to increase the capacity and abilities of MSME players and facilitate the process of processing business legalization such as permits, MUI certificates, halal and so on. The two efforts that have been carried out by the Department of Cooperatives and SMEs include providing training to MSMEs, both technical training and training to increase the insight of MSME players. Third, efforts to implement the MSME development program carried out by the Sikka Regency Cooperative and SME Service have not been effective due to various obstacles, namely internal factors such as a lack of budget for coaching assistance, as well as external factors such as a low entrepreneurial spirit, the level of consumption of products produced by MSMEs also low, as well as low marketing of local products produced by MSMEs.